Evaluation of the multiplex PCR combined with capillary electrophoresis technique for detecting pathogenic bacteria and antibiotic resistance genes in bone infections - Junye Liu; Yan Yu; Wei Feng; Zhihao He; Mengfei Wang; Weikun Hou; Yannan Zhao; Yi Liu; Yuzhu Yan; Heping Zhao (BMC Infectious Diseases)
Abstract Objective Orthopedic wound infection is a difficult problem in the clinic. Accurate and rapid microbiological test results are essential for case management, antibiotic therapy, and infection control. Methods We retrospectively evaluated 1285 specimens (puncture fluid, catheter, secretions, joint fluid, lavage fluid, extraction fluid, blood culture, drainage fluid, cerebrospinal fluid, bone, prosthesis tissue, etc.) from 739 patients who received orthopedic diagnosis and treatment, using routine conventional method (RCM)s as a reference method to evaluate the performance of multiplex PCR combined with capillary electrophoresis (mPCR-CE) for detecting pathogens and antibiotic resistance genes associated with bone infection. Results Among the 1285 samples analyzed, 1045 samples were consistent with the results of the RCM, with an agreement rate of 81.32%. Among the 155 inconsistent results, 13 (1.01%) were mPCR-CE negative but RCM positive, 142 (11.05%) was mPCR-CE positive but RCM negative. Compared with RCM, mPCR-CE demonstrated positive percentage and negative percentage agreement values of 65.37% and 98.35%, respectively. Moreover, the detection rate of multidrug-resistant bacteria by the mPCR-CE method was generally better than that by the RCM method. The detection rate of methicillin-resistant Staphylococcus aureus (MRSA) by the mPCR-CE method is relatively high. The traditional drug-sensitive culture method is more inclined to detect extended-spectrum β-lactamases (ESBLs). The mPCR-CE method has obvious advantages in terms of timeliness. Conclusion This study revealed that mPCR-CE is a new and effective diagnostic method that can significantly reduce the identification time of bacterial identification and drug resistance, and has the potential to improve the management of orthopedic infections.